The legacy of ZikaPLAN: a transnational research consortium addressing Zika - Annelies Wilder-Smith; Elizabeth B. Brickley; Ricardo Arraes de Alencar Ximenes; Demócrito de Barros Miranda-Filho; Celina Maria Turchi Martelli; Tom Solomon; Bart C. Jacobs; Carlos A. Pardo; Lyda Osorio; Beatriz Parra; Suzannah Lant; Hugh J Willison; et al. (Global Health Action, 2021)
Global health research partnerships with institutions from high-income countries and low- and middle-income countries are one of the European Commission’s flagship programmes. Here, we report on the ZikaPLAN research consortium funded by the European Commission with the primary goal of addressing the urgent knowledge gaps related to the Zika epidemic and the secondary goal of building up research capacity and establishing a Latin American-European research network for emerging vector-borne diseases. Five years of collaborative research effort have led to a better understanding of the full clinical spectrum of congenital Zika syndrome in children and the neurological complications of Zika virus infections in adults and helped explore the origins and trajectory of Zika virus transmission. Individual-level data from ZikaPLAN`s cohort studies were shared for joint analyses as part of the Zika Brazilian Cohorts Consortium, the European Commission-funded Zika Cohorts Vertical Transmission Study Group, and the World Health Organization-led Zika Virus Individual Participant Data Consortium. Furthermore, the legacy of ZikaPLAN includes new tools for birth defect surveillance and a Latin American birth defect surveillance network, an enhanced Guillain-Barre Syndrome research collaboration, a de-centralized evaluation platform for diagnostic assays, a global vector control hub, and the REDe network with freely available training resources to enhance global research capacity in vector-borne diseases.